Evaluation of knowledge and attitude related to anemia among female utar undergraduate students: a cross-sectional study - Lock, Yee Sin (2023)
Anemia or iron deficiency is one of the most prevalent medical around the whole especially among female population due to several underlying reasons related. Still, there has been very limited investigation of anemia or iron related knowledge and attitudes among undergraduate students in Malaysia. Hence, this study conducted as to assess the knowledge and attitude related to anemia or iron among undergraduate students in Universiti Tunku Abdul Rahman (UTAR). A cross-sectional study design with convenience sampling method was adopted by using validated survey among 171 female undergraduate students whereby the questionnaire uncomposed of knowledge and attitude related to anemia or iron were self-administered through social platforms. The data obtained were later analyzed using SPSS version 27.0 in the form of descriptive and inferential statistics. The associations between knowledge and attitude, knowledge and attitude with selected demographic variables were analyzed using the Chi-square test and Spearman’s rho correlation test was used to determine the strength and direction of the knowledge and attitude variables. Among 171 students, the majority (70.2%) had poor knowledge but a neutral iii attitude (60.8%) related to anemia or iron in which average score were 46.51% and 73.33% respectively. The knowledge was moderately associated with the attitude (r = 0.403, p < 0.001). Age showed a statistically significant association with knowledge but not with attitude (p = 0.032; p = 0.111). The average menstruation duration was associated statistically with the knowledge (p = 0.041). The knowledge level was compared between study fields (health and non-health science) and found a significant association (p < 0.001). Further studies are needed to strengthen the existing findings from previous studies. Information from this study can be used as a reference to raise awareness regarding the importance of anemia prevention which is essential to help improve women’s quality of life